Agrotourism Literacy of Based on Sipakatau, Sipakalebbi, Silapaknge (3S) in Supporting the Village's Sustainable Development Goals in Tellu Boccoe Village, Ponre District, Bone Regency - Erwing, Erwing; Ilham, Muh.; Ningsih, Irma Ayu; Yusuf, Andi Nurfaizah; Andriana, Angga (Budapest International Research and Critics University, 2022)
The purpose of the final report on the holistic village development and empowerment program is to find out and analyze edu-agrotourism literacy of based on Sipakatau, Sipakalebbi, Silapaknge (3S) in supporting the village's sustainable development goals in Tellu Boccoe Village, Ponre District, Bone Regency. The implementation method of the holistic village development and empowerment program on training of making kartello, gutello, instant sarebba, and education on pine forest conservation tourism is a series of stages that are arranged systematically. The result of the final report is the implementation of the holistic village development and empowerment program in the form of training on the manufacture of kartello, gutello, instant sarebba, and education on pine forest conservation as an effort to utilize the existing natural potential as well as a means of improving the community's economy through counseling, training, and mentoring activities. In addition, the sustainability of the holistic village development and empowerment program by disseminating products to the wider community and expanding access to promotion and marketing is expected to be able to improve the community's economy, to make the village economy independent, in addition to this program as an effort to preserve the Bugis Bone culture.